Social sensitization of breast cancer by the directorates of social activity - Ikoufane, Chafik (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales, 2020)
Health issues are among the most important programs that Algerian institutions aim to disseminate and raise in the community, especially breast cancer, which has spread significantly in the recent period. Since the geographical distribution of the population between urban and rural areas may affect the equitable distribution of the sensitization and prevention process, social activity plays a key role. Based on statistical and descriptive analytical methods, the study aims to know the relationship between geographical regions and communication strategy of social activity by directorates on sensitization about breast cancer, and the opinions or attitudes of women about sensitization campaigns and its ability to prevent women from cancer, to evaluate the sensitization programs through statistics provided by official institutions and bring solutions to improve existing programs.